The Justice Dilemma of Punishment and Rehabilitation in the Juvenile Criminal Justice System - Luciana Luciana; Rizki Tri Anugrah Bhakti; Dwi Afni Maileni; Indra Sakti (Indonesian Journal Publisher, 2026)
This study examines the justice dilemma between punishment and rehabilitation in the Juvenile Criminal Justice System (Sistem Peradilan Pidana Anak/SPPA) and formulates a more proportional legal reasoning standard for handling children in conflict with the law. The research employs a normative juridical method using statutory and conceptual approaches, supported by doctrinal analysis and relevant scholarship on retributive, rehabilitative and restorative justice. Legal materials are analyzed through systematic and teleological interpretation, as well as prescriptive legal argumentation, to assess the relationship between child protection, victims’ interests and the legitimacy of punishment. The findings show that the central dilemma lies not in the existence of punishment or rehabilitation per se, but in the absence of consistent argumentative standards to determine when punishment may be justified and when rehabilitation should be prioritized. The study finds that punishment remains legally possible within SPPA, but its legitimacy must be strictly limited by necessity review, the ultimum remedium principle and proportionality. Conversely, rehabilitation and diversion should not be treated merely as policy preferences, but as normative priorities because they are aligned with the best interests of the child and social reintegration objectives. This study formulates an operational normative reasoning framework requiring law enforcers to assess the purpose of intervention, the availability of alternatives, procedural quality and the justificatory basis of decisions. These findings contribute to strengthening consistency in SPPA implementation and to developing a more accountable, humane and just juvenile justice practice.